BERPIKIR RASIONAL WARGA BELAJAR DI SATUAN PENDIDIKAN NON FORMAL SANGGAR KEGIATAN BELAJAR (SPNF-SKB) KOTA PEKANBARU - Apris Irhami; Daeng Ayub; Titi Maemunaty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract : Rational thinking is a thought that uses reason or logic for what happens to find the truth, which becomes a yardstick for making decisions. It is hoped that one can use logic based on relevant evidence to form ideas, attitudes, actions, in order to achieve goals. Found several phenomena on Non-Formal Education Unit of the Pekanbaru city Learning Center (SPNF-SKB) such as not being able to argue, have no motivation, and cannot take risks for the actions taken. This phenomenon is also related to the attitude of learning citizens and supportive teaching human resources. The purpose of this study was to determine the way of thinking of the SPNF-SKB learning community.This type of research used in this research is descriptive with a quantitative approach. The number of citizens studying in the non-formal education unit of the Pekanbaru city learning center was 70 people consisting of 10 packages A, 23 packages B, and 37 packages C. The sampling technique was random sampling method of 41 people for the questionnaire test. Research indicators are the formation of understanding, forming opinions, and drawing conclusions.Based on the research results brational thinking citizens learn in non-formal education units, learning activity centers (SPNF-SKB) Pekanbaru city is classified as good, with the highest indicator for opinion formation with 74%, while the indicator for understanding formation with a percentage of 71% and indicators for drawing conclusions with a percentage of 63%.Key Words : Rational Thinking, Learning Citizens, SKB